Improving Family Ties and Adolescent Relationships in Open Schooling (London Journal of Research In Humanities and Social Sciences, 2024)
.In this paper, we attempt to clarify the concept of open school and to highlight relevant actions and main characteristics. A school can be described as open when a culture of cooperation and mutual trust prevails among students, teachers and parents. Hereby, a pedagogical practice is presented that was implemented in two sections of the 1st class at the 1st Lyceum of Spata , with the aim of a) preventing intra-school violence cases, b) fostering the integration and inclusion of foreign students by looking at common adolescent concerns and problems, and c) strengthening the institution of the family. The action, which took place at the beginning of the 2023-2024 school year and is expected to be completed at the end of January, was accompanied by a sample survey using questionnaires answered by 47 students, 28 teachers and 36 parents. The students were given a questionnaire before and after the action to identify the effects of the pedagogical practice. Of particular interest are the answers to the questionnaire given to the students after the action.? part of the action was presented on January 20 at the International conference "learning from the extremes"
Keywords: teaching practices; school volleyball; verbal intervention; didactic regulation; acceptance and inclusion of refugee students; acceptance and respect for otherness; cooperation; empathy and emotional intelligence; experiential learning; open school; reduction in intra-school violence; strengthening of family ties.